2020
DOI: 10.3390/cancers12103021
|View full text |Cite
|
Sign up to set email alerts
|

Progression-Free Survival and Overall Survival in Patients with Advanced HER2-Positive Breast Cancer Treated with Trastuzumab Emtansine (T-DM1) after Previous Treatment with Pertuzumab

Abstract: The approval of trastuzumab emtansine (T-DM1) was conducted without pertuzumab as previous therapy. Efficacy data on T-DM1 following pertuzumab treatment are therefore limited. This study explores this issue in a real-world setting. Within the prospective PRAEGNANT (Prospective Academic Translational Research Network for the Optimization of the Oncological Health Care Quality in the Advanced Setting) metastatic breast cancer registry (NCT02338167), patients in all therapy lines receiving any kind of treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…In the EMILIA study, the median PFS with T-DM1 was 9.6 months, but it must be remembered that these patients did not receive prior treatment with pertuzumab. Corresponding data from real-world registries are similar to the DESTINY-Breast03 trial, in which the median PFS was 7.7 months in second-line therapy after prior treatment with pertuzumab and 3.4 months in third-line therapy 25 . Hence, in this therapeutic setting, T-DXd significantly improved the treatment of HER2-positive breast cancer.…”
Section: Still Significant Progress In the Treatment Of Her2-positive...mentioning
confidence: 72%
See 1 more Smart Citation
“…In the EMILIA study, the median PFS with T-DM1 was 9.6 months, but it must be remembered that these patients did not receive prior treatment with pertuzumab. Corresponding data from real-world registries are similar to the DESTINY-Breast03 trial, in which the median PFS was 7.7 months in second-line therapy after prior treatment with pertuzumab and 3.4 months in third-line therapy 25 . Hence, in this therapeutic setting, T-DXd significantly improved the treatment of HER2-positive breast cancer.…”
Section: Still Significant Progress In the Treatment Of Her2-positive...mentioning
confidence: 72%
“…Therapielinie 7,7 Monate nach einer Vorbehandlung mit Pertuzumab und 3,4 Monate in der 3. Therapielinie betrug 25 . Somit konnte in dieser Therapiesituation mit T-DXd die Behandlung des HER2-positiven Mammakarzinoms deutlich verbessert werden.…”
Section: Weiterhin Bedeutsame Fortschritte Bei Der Behandlung Von Pat...unclassified
“…In the PRAEGNANT metastatic breast cancer registry, 76 patients were treated with T-DM1 in different lines after taxane-trastuzumab-pertuzumab (39 in second-line, 25 in third-line and 12 in fourth-line or higher). This study found a median PFS with T-DM1 of 3.5 months in all patients but with a decline of PFS when T-DM1 was administered in later lines (median PFS of 7.7 months in second-line, 3.4 months in third-line and 2.7 months in fourth-line or higher) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15% of breast cancers overexpress ErbB2/Her2 receptor tyrosine kinase [1] and are normally treated with ErbB2targeted drugs [2,3]. Approximately 20% of such malignancies develop resistance to these agents and become incurable [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 15% of breast cancers overexpress ErbB2/Her2 receptor tyrosine kinase [1] and are normally treated with ErbB2targeted drugs [2,3]. Approximately 20% of such malignancies develop resistance to these agents and become incurable [2,3]. Conceivably, treatment efficacy of ErbB2-positive cancers could be facilitated by drugs blocking oncogenic mechanisms downstream of ErbB2.…”
Section: Introductionmentioning
confidence: 99%